REKAMAN STASIUN GPS SEBAGAI PENDETEKSI PERGERAKAN TEKTONIK, STUDI KASUS: BENCANA TSUNAMI ACEH 26 DESEMBER 2004 - Fajar Rizki Widiatmoko; Akhmad Zamroni; Muhammad Abdurrozak Siamashari; Afifah Nurul Maulina (Jurnal Sumberdaya Bumi Berkelanjutan (SEMITAN), 2019)
Geographic Position System (GPS) is an electronic instrument that is used to determine the position of coordinates, with the help of the triangulation of satellite signals it can be accurately determined the coordinates of the position. An embedded GPS station is built to track changes in station positions over a period of time. Changes in position over a period of time are calculated using the GPS kinematic method and summed up simply using the GPS velocity method. International GNSS Service (IGS) is a global GPS data provider service with time-per-second densities and millimeter accuracy. During the Aceh tsunami tragedy 26 December 2004 00.58'.53 "UTC there were 3 GPS stations, each located on a different tectonic plate, the JOGJ station located in Yogyakarta representing the Micro-Sunda plate, the ISSC station located in India representing the Indian plate, and the DGAR station located in the Maldives represents the Eurasian plate as a stable site. The results of data analysis showed that there were 4 phases of tectonic movements during the Aceh tsunami tragedy, anomalous movement phases, pressuring phases, release phases, and stabilization phases. The tectonism study using the GPS station data approach can be used as a parameter to detect plate movement data, especially a great hope for the development of earthquake detection studies.   Keywords: GNSS, GPS Kinematic, GPS Velocity, Plate movement, Tsunami trigger Geographic Position System (GPS) adalah suatu intrumen elektronik yang digunakan untuk mengetahui posisi kordinat, dengan bantuan triangulasi sinyal satelit maka dapat ditentukan posisi kordinat secara akurat. Stasiun GPS tertanam dibangun untuk mengetahui perubahan posisi stasiun dalam kurun waktu tertentu. Perubahan posisi dalam kurun waktu tertentu dihitung menggunakan metode GPS kinematic dan disimpulkan secara sederhana menggunakan metode GPS velocity. International GNSS Service (IGS) adalah layanan penyedia data GPS seluruh dunia dengan kerapatan waktu per-detik dan akurasi dalam milimeter. Pada tragedi bencana tsunami Aceh 26 Desember 2004 00.58’.53” UTC terdapat 3 stasiun GPS yang masing-masing berlokasi pada lempeng tektonik yang berbeda, stasiun JOGJ berlokasi di Yogyakarta mewakili lempeng Micro-Sunda, stasiun ISSC berlokasi di India mewakili lempeng Hindia - Australia, dan stasiun DGAR berlokasi di Maldives mewakili lempeng Eurasia sebagai stable site. Hasil analisa data menunjukan terdapat 4 fase gerakan tektonik selama tragedi tsunami Aceh, fase gerakan anomali, fase penekanan, fase pelepasan dari tekanan, dan fase penstabilan. Studi tektonisme menggunakan pendekatan data stasiun GPS bisa dijadikan parameter data pendeteksi pergerakan lempeng, terutama sebuah harapan besar pengembangan studi pendeteksi gempa bumi.Kata kunci: GNSS, GPS Kinematik, GPS Velocity, Pergerakan lempeng, Pemicu Tsunami